The impact of the official basketball Champions League game on lower-body neuromuscular performance characteristics - Cabarkapa, D.; Cabarkapa, D. V.; Aleksic, J.; Mihajlovic, F.; Fry, A. C. (The Journal of Strength and Conditioning Research, 2024)
Considering the extensive use of force plate technology in an applied sports setting and the lack of scientific literature during the actual competition, the purpose of the present study was to investigate the acute impact of an official basketball game on lower-body neuromuscular performance characteristics. Eight professional male basketball players volunteered to participate in this investigation. Upon completion of a standardized warm-up procedure, each athlete performed 3 maximum-effort countermovement vertical jumps (CVJs) with no arm swing while standing on a uniaxial force plate system sampling at 1,000 Hz. Then, 3 days after the baseline testing procedures, the athletes completed an identical CVJ testing protocol immediately after the completion of an official basketball game. Paired sample t-tests were used to examine statistically significant pregame and postgame differences in CVJ performance (p < 0.05). The findings reveal that force-time metrics examined during both eccentric and concentric phases of the CVJ tend to remain relatively unchanged in response to the game stimulus. Also, no differences in outcome metrics such as vertical jump height and reactive strength index-modified have been observed. However, despite not reaching the level of statistical significance, it should be noted that eccentric peak velocity, force, and power did demonstrate a moderate decrease postgame when compared with the baseline measurements (g = 0.509-0.627), suggesting that the eccentric phase of the jumping movement might be more sensitive in detecting acute fatigue-induced performance changes within this specific group of professional athletes.